Surface morphology engineering of metal-oxide films by chemical spray pyrolysis - Rodriguez, J (2007)
This work has been financially supported by the International Program for Physical Science of Uppsala University (IPPS), the Instituto de Investigacion of Universidad Nacional de Ingenieria, and CONCYTEC (Peruvian Research Council).